2023
DOI: 10.1590/1413-81232023283.14362022
|View full text |Cite
|
Sign up to set email alerts
|

Remote work and back pain during the COVID-19 pandemic in adults and older population in South Brazil

Abstract: This article aims to investigate the association between remote work and Back Pain during the COVID-19 pandemic, and to analyze this relationship according to the body mass index. Population-based, cross-sectional study carried in two cities in southern Brazil, in individuals aged 18 years and over. Data were collected through household interviews from October to January 2020/21. Outcomes: back pain (cervical, thoracic, lumbar/acute, chronic) and pain intensity. Exposure variable: remote work. For the analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
1
1
4
Order By: Relevance
“…Sendo 13 destes artigos submetidos a análise qualitativa sobre a questão de pesquisa. A tabela Domínguez, 2022;Fadel et al, 2023;Guimarães et al, 2022;Lunde et al, 2022;Radulovic et al, 2021;Saes-Silva et al, 2022;Tellez et al, 2022;Tezuka et al, 2022). Sob esta nova realidade, o teletrabalho, veio junto a uma gama de problemas ergonômicos, caracterizados por movimentos repetitivos, posturas inadequadas em período extenso, esforço físico, aumentando o risco de problemas musculoesqueléticos, isso pode ser evidenciado nos estudos de (Batista, Melcher e Carvalho, 2022;Fadel et al, 2023;Guimarães et al, 2022;Saes-Silva et al, 2022;Tellez et al, 2022).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Sendo 13 destes artigos submetidos a análise qualitativa sobre a questão de pesquisa. A tabela Domínguez, 2022;Fadel et al, 2023;Guimarães et al, 2022;Lunde et al, 2022;Radulovic et al, 2021;Saes-Silva et al, 2022;Tellez et al, 2022;Tezuka et al, 2022). Sob esta nova realidade, o teletrabalho, veio junto a uma gama de problemas ergonômicos, caracterizados por movimentos repetitivos, posturas inadequadas em período extenso, esforço físico, aumentando o risco de problemas musculoesqueléticos, isso pode ser evidenciado nos estudos de (Batista, Melcher e Carvalho, 2022;Fadel et al, 2023;Guimarães et al, 2022;Saes-Silva et al, 2022;Tellez et al, 2022).…”
Section: Resultsunclassified
“…A tabela Domínguez, 2022;Fadel et al, 2023;Guimarães et al, 2022;Lunde et al, 2022;Radulovic et al, 2021;Saes-Silva et al, 2022;Tellez et al, 2022;Tezuka et al, 2022). Sob esta nova realidade, o teletrabalho, veio junto a uma gama de problemas ergonômicos, caracterizados por movimentos repetitivos, posturas inadequadas em período extenso, esforço físico, aumentando o risco de problemas musculoesqueléticos, isso pode ser evidenciado nos estudos de (Batista, Melcher e Carvalho, 2022;Fadel et al, 2023;Guimarães et al, 2022;Saes-Silva et al, 2022;Tellez et al, 2022). Como consequência, multiplicaram-se as queixas de condições como cefaleia, cervicalgia, lombalgia e dores articulares em ombros, joelhos e quadris (Alfaia et al, 2022;Ap et al, 2013;Cristancho, Barrera e Castellanos-Domínguez, 2022;Fadel et al, 2023;Fernandes e Salgueiro, 2022;Gomez et al, 2022;Guimarães et al, 2022;Minoura et al, 2019;Papalia et al, 2022;Saes-Silva et al, 2022;Santos et al, 2021;Tellez et al, 2022;Tezuka et al, 2022;Vcw et al, 2018).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Another study highlighted the importance of BMI in the context of spinal pain. The aim of an article, published in 2023 [ 8 ], was to examine the relationship between remote work and the incidence of back pain during the COVID-19 pandemic, and to analyze this relationship based on body mass index. In the study group, approximately one in four remote workers reported back pain during the COVID-19 pandemic.…”
Section: Risk Factorsmentioning
confidence: 99%